PENGEMBANGAN MODUL PEMBELAJARAN GEORGRAFI BERBASIS LITERASI SAINS - Parlina, Ade Apin; Ruhimat, Mamat; Waluya, Bagja (Universitas Nahdlatul Ulama Blitar, 2025)
This research aims to develop geography teaching materials based on scientific literacy, suitable for independent use and easy to understand, particularly in the atmosphere. Developing these literacy-based modules takes into account the curriculum content implemented in Indonesia and the PISA framework for scientific literacy, which includes indicators such as explaining phenomena scientifically, designing and evaluating scientific investigations, and interpreting data. The study used the R&D method with a 3D model of the Define, Design, and Develop phases. The development process involved validation tests by experts and students. Validation tests with students were carried out in two stages: the first stage involved two small groups, comprising students with high academic abilities and students with prior experience as participants in the AKM (Minimum Competency Assessment) and AKMI (Islamic Education Competency Assessment) and AKMI (Islamic Education Competency Assessment). The second stage involved a larger group of 32 randomly selected students with low, medium, and high academic abilities. The results showed that the module achieved validation scores of 84% from subject matter experts, 85% from media experts, and 84% for readability from students. These results indicate that the teaching module is highly suitable for use. This research implies that the developed teaching module can be utilized in geography learning, particularly on the topic of the atmosphere, through a scientific approach integrated with scientific literacy.